Advertisement call of Scinax strigilatus (Spix, 1824) (Anura: Hylidae) from southern Bahia, Brazil - Mendes, Caio Vinicius De Mira; Junior, Euvaldo Marciano; Ruas, Danilo Silva; de Oliveira, Renan Manoel; Solé, Mirco (Zootaxa, 2013)
Scinax strigilatus (Spix, 1824) is a member of the Scinax catharinae species group that inhabits forested streams in the Atlantic Rainforest of southern Bahia, northeastern Brazil. The loss of the holotype resulted in years of nomenclatural confusion solved with the designation of a neotype and the redescription of the species by Pimenta et al. (2007). Aiming to contribute to the taxonomic status and natural history of the species, we describe herein the advertisement call of Scinax strigilatus (Fig. 1A).